COVID-19 Diagnostics Outside and Inside the National Health Service: A Single Institutional Experience - Lukasz Fulawka (MDPI AG, 2021)
The COVID-19 epidemic has been going on continuously for more than 1.5 years. Fast and reliable diagnosis is a key component of an outbreak response strategy. Our goal is to present the statistics from one of the diagnostic points of a large city in Poland. Swabs of the throat or nasopharynx of people reporting for molecular diagnostics of SARS-CoV-2 presence were taken. CE-IVD-certified RNA isolation and RT-PCR assays were used. According to our data, the prevalence of SARS-CoV-2 infection in the examined population equaled 14.7%; however, large differences were observed depending on where the sampling point was located: as much as 50.3% of positive results for samples collected at a stationary point, 36.2% for samples from inpatients and hospital staff, and only 8.9% for samples from patients whose test was paid by their employer. The age structure of the infected population was fairly even, with a slightly higher number of people over 50 years of age. Men were examined more often, but it was among women that a higher percentage of infection was recorded. Every fifth test was performed for a foreigner, but compared to Poles, a much lower incidence of infection was found in these samples. We conclude that due to the high prevalence of infection in patients from social care centers and in those referred to hospitals, it is recommended that a special sanitary regime is followed in those settings. We will evaluate the effectiveness of vaccinations, expecting that the coming months bring positive changes in the statistics on prevalence.